Sensory overdrive : deluxe edition - Monroe, Michael, 1962-; Yaffa, Sami, 1963-; Wildheart, Ginger, 1964-; Conte, Steve; Rockfist, Karl; Williams, Lucinda, 1953-; Kilmister, Lemmy, 1945-2015 (2011)
13 kappaletta.
Trick of the wrist ; '78 ; Got blood? ; Superpowered superfly ; Modern day miracle ; Bombs away ; All you need ; Later won't wait ; Gone baby gone ; Center of your heart ; Debauchery as a fine art ; Another night in the sun ; You're next.
Michael Monroe (lauluääni, soittimet), Sami Yaffa (sähköbasso), Ginger (kitara), Steve Conte (kitara), Karl Rockfist (rummut). Lisäksi: Lucinda Williams (lauluääni raidalla 9), Lemmy Kilmister (lauluääni raidalla 11). - Taustalaulu: Monroe, Yaffa, Ginger, Conte, Rockfist.